2010
DOI: 10.1103/physrevb.81.054515
|View full text |Cite
|
Sign up to set email alerts
|

Hall effect in superconductingFe(Se0.5Te0.5)thin films

Abstract: The Hall effect is investigated for eight superconducting Fe(Se 0 (typically T c > 9 K), R H leaves almost unchanged down to T ≈ 100 K, and then starts decreasing toward a negative side. Around the temperatures when R H changes its sign from positive to negative, obvious nonlinearity is observed in the field-dependence of Hall resistance as to keep the low-field R H positive while the high-field R H negative. Thus the electronic state just above T c is characterized by n e (electron density) > n h (hole densit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
42
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 25 publications
7
42
1
Order By: Relevance
“…Figure 4(d) demonstrates that the R H of all three films is almost temperature independent from 80 K to room temperature. This phenomenon is similar to that in both films819 and single crystal20. In the low temperature regime below 80 K, R H for all three films shows an obvious divergence with temperature.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Figure 4(d) demonstrates that the R H of all three films is almost temperature independent from 80 K to room temperature. This phenomenon is similar to that in both films819 and single crystal20. In the low temperature regime below 80 K, R H for all three films shows an obvious divergence with temperature.…”
Section: Resultssupporting
confidence: 83%
“…The reduction in anion height could, in turn, affect the density of states (DOS) at the Fermi energy ( E F ) and the carrier density28, by tuning the overlap between the Te 5 p (Se 4 p ) and Fe 3 d orbits. It should be noted that the sign reversal from positive to negative in R H ( x = 0.6) should be considered as an intrinsic property for high T C samples in the 11 system, which has been found in high-quality thin film19 and single crystal samples29. Our results thus highlight the role of structural parameters in the determination of charge carrier behaviour because both the AFM order and the modification of the Fermi surface show a strong relationship with anion height2324.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, although Liu et al 14 reported that bulk superconductivity resides only in the region of Se level higher than 29%, it was observed in the Se doping level between 10 and 50% by Noji et al 2223. As for the Hall coefficient, conflicting low-temperature behaviors have been observed in crystals with nominally the same amount of Se242526. Even in the case of resistivity, both the metallic and nonmetallic behaviors were reported, and the absolute value just above T c has a spread from 200 to 1500 μΩ cm1223242526.…”
mentioning
confidence: 99%
“…As for the Hall coefficient, conflicting low-temperature behaviors have been observed in crystals with nominally the same amount of Se242526. Even in the case of resistivity, both the metallic and nonmetallic behaviors were reported, and the absolute value just above T c has a spread from 200 to 1500 μΩ cm1223242526. These controversies are believed to come from the sample-dependent Fe nonstoichiometries1527, which originate from the partial occupation of the second Fe site (excess Fe site) in the Te/Se layer.…”
mentioning
confidence: 99%
“…Therefore, it is interesting to study the biaxial strain effect of FST in FST/PMN-PT heterostructures. Up to now, there has been no report on FST/PMN-PT heterostructures although there have been some work on FST thin film grown on non-ferroelectric substrates52021. Moreover, there is a large lattice mismatch between FST ( a  = 3.814 Å) and PMN-PT ( a  = 4.02 Å)2223, so tensile strain is induced in FST and this strain decreases from the interface to the surface of FST.…”
mentioning
confidence: 99%